Sequence of residential building construction in 99 days - Durgalakshmi, S; Mahendran, K (International Journal of Engineering and Technology, 2018)
Time management is one of the vital key factor in the project management of any construction project. Effective planning, scheduling & control of construction project resulted in the reduction of construction time, cost overrun and disputes. Not only effective planning, but also proper organization & sufficient flow of resources to a project can automatically achieve a good result when preliminary works has been done for each & every activity. The study area mainly focuses on the execution of work as it is scheduled before the commencement of construction. This paper describes the sequence of residential building construction (G+2) in 99 days has been executed as a real time project and achieved the completion in 99 days. For normal construction of (G+2) may be completed in 180days, but this project completed in 99 days by using the technique called Task Based Activity Execution (TBAE) to the labours. During execution, delays are observed and overcome by using the preliminary works for the next activity. The sequence of construction discussed here will definitely enhance the project planning skills for the forthcoming project.